ANALYSIS OF PROMOTION MIX ELEMENTS: A CASE STUDY OF E-SPPT BY BOGOR CITY REGIONAL REVENUE AGENCY - Putri, Kartika Anggraeni Sudiono (Universitas PGRI Semarang, 2024)
e-SPPT of Land and Building Tax (PBB) has an important role in regional development. e-SPPT, which has been socialized by Bogor City Regional Revenue Agency (called BAPENDA), has not been implemented optimally because there are still many taxpayers who do not know about the service innovation. This research focuses on revealing the promotion mix strategy implemented by BAPENDA Bogor City in socializing e-SPPT PBB and identifying obstacles to implementing the promotion mix in the e-SPPT PBB service.This research uses a qualitative approach with a case study type. The method is used to collect evidence through interviews, documentation, and observation. Interviews were conducted with six informants, namely three sources from internal parties and three sources from taxpayers. To validate the data, the source triangulation technique was used. The research results show that the activity of promoting e-SPPT PBB to taxpayers has been implemented through four of the six promotion mixes described by Belch and Belch (2021), namely advertising, internet marketing, direct marketing, and personal selling. Meanwhile, several obstacles were found, namely the lack of intensity of the socialization techniques that had been used, so that they had not been able to reach all taxpayers. Suggestions to related agencies are to add other socialization or promotional strategies, such as strengthening public relations through publicity and holding events, so that they can increase awareness and encourage taxpayers to pay taxes.